The impact of tropical cyclone outer size on ocean surface responses - Ruan, Zhenxin; Li, Bo; Yu, Chengcheng; Ding, Ruibin; Bai, Peng; Wu, Qiong (Frontiers in Marine Science, 2024)
We used daily sea surface temperature (SST) data and hourly drifter data to investigate ocean responses to tropical cyclone (TC) intensity and outer size (wind radius of 34 kt, or R34) in the Northwest Pacific. Results showed that SST cooling is more sensitive to TC R34 than to TC intensity; namely, TCs with a larger R34 cause stronger SST cooling regardless of their intensity. TCs with an R34 ≥125 nmi could cool SST 0.9°C more than TCs with an R34<125 nmi. Drifter data indicated that TCs generate a large current with near-inertial periods. The filtered near-inertial currents were used to calculate the time series of near-inertial kinetic energy Ef, and found that TCs with a larger R34 will trigger stronger Ef. Further analysis revealed that the non-dimensional storm speed S, which is defined as the ratio of the local near-inertial period to the residence time of the TC, is correlated closely with the amplitude of SST cooling when R34 is used to quantify the scale of the TC. Most TCs have a residence time smaller than the local near-inertial period, and therefore, TCs with a large R34 have longer residence times and are closer to the local near-inertial period, which is favorable for stronger SST and current responses. This impact of TC outer size on the surface ocean response implies the critical role of TC outer size in ocean processes under a TC background.